The Theory of Therapeutic Communalism: A Communicative Framework for Proactive Crime Prevention - Ijiomah, Amarachukwu Onyinyechi (dialektika kontemporer, 2025)
Contemporary criminal justice systems operate predominantly within a reactive paradigm, intervening only after legally cognizable offenses have been committed. This temporal positioning fundamentally limits their capacity to address the psychosocial, relational, and communicative antecedents that precede criminal behavior. This article advances the Theory of Therapeutic Communalism, a novel socio-legal framework that reconceptualizes crime prevention and recidivism reduction as emergent properties of intentional, empathetic, and healing-centered communication within communities. Building upon the foundational insights of Therapeutic Jurisprudence developed by David B. Wexler and Bruce J. Winick (Wexler & Winick, 1996), the theory extends therapeutic reasoning beyond formal legal institutions into the micro-social fabric of everyday communal life. It posits that early conversational intervention, cultivated collective responsibility, and empathetic dialogue within social networks can interrupt criminogenic pathways during their developmental stages, thereby preventing harm before formal legal intervention becomes necessary. The article systematically delineates the theory’s intellectual genealogy, core theoretical assumptions, operationalizable components, and practical applications across diverse social institutions. By situating crime prevention within the relational dynamics of daily interaction, Therapeutic Communalism offers a human-centered, sustainable, and cost-effective complement to traditional punitive models, contributing a significant preventive dimension to socio-legal scholarship and public safety policy.